REFINED ESTIMATES OF DIRECT PYROGENIC CARBON EMISSIONS IN RUSSIAN FORESTS BASED ON REMOTE MONITORING DATA FROM 2011 TO 2023 - D. V. Ershov; E. N. Sochilova; K. A. Kovganko (Вопросы лесной науки)
The paper presents refined estimates of direct carbon emissions from forest fires in Russia based on satellite data for the period from 2011 to 2023. The main differences from the estimates in previous our publications are the use of a new version of annually updated products of pre-fire forest combustible fuels (FCF), which include new data on the reserves of FCF in the upper tree canopy, undergrowth, living ground vegetation cover and wood debris. In addition, we use new products of forest species and age structure, the level of fire damage to forest vegetation for mapping the type and fire severity, and the coefficients of fuel consumption in wood debris. As a result of the above changes in the data and the calculation algorithm for the thirteen-year period, the average annual pyrogenic emission is 107.4 ± 56.7 MtC year-1 or 393.7 ± 207.9 CO2 equivalent. The obtained estimates of direct Carbon emissions from fires are comparable with international data. In anomaly years of 2012 and 2021, emissions from forest fires amounted to 250.8 and 175.1 MtC or 919.6 and 642.2 MtCO2, respectively. The last two years have been detected by low forest burning and fire intensity, due to which, within the boundaries of the studied interval of years, a trend towards a decrease in pyrogenic emissions by 12 MtCO2-equivalent per year relative to the long-term average is observed.